Employees’ Tenure and Length of Service and Performance: A Case Study on the Moderating Role of Psychological Empowerment among Supervisors - Sanjeev Janardhanan; Santhi Raghavan

(untitled)
Employee productivity is extremely crucial in today’s business environment. In order to achieve high productivity, companies need to have a team of high performing employees. This empirical study explores the influence of employees’ tenure in an organisation together with their academic background in the relationship towards improving and enhancing their performance. The study also looks into whether psychological empowerment has any influence on the relationship between their tenure and academic background and performance. Respondents for this research were from the supervisory staff from Malaysia’s glazed ceramic tile industry. The results of the study have shown that employees’ academic background and their tenure at their organisations have an influence on their performance but in the presence of psychological empowerment, both demographic variables do not improve performance. (Abstract by authors)